Analytical model for predicting the post-fire bond behavior between steel bars and concrete. (8th August 2022) - Wang, Tian-Ci; Gao, Wan-Yang; Hu, Li-Li; Hamed, Ehab; Bai, Yu-Lei; Zeng, Jun-Jie; Yang, Jian
Highlights: An analytical model is proposed to investigate the post-fire bond behavior between steel bars and concrete. Residual bond strengths of steel bars can be accurately predicted by the proposed analytical model. A temperature-dependent local bond-slip model is developed and verified through the comparisons between numerical and experimental results. Abstract: Bond behavior between steel bars and concrete is likely to be significantly degraded after exposure to high temperatures in a fire, which will influence the residual strength of the reinforced concrete (RC) member and the selection of appropriate repair and strengthening solutions. This paper presents an analytical model for predicting the bond behavior between steel bars and concrete after exposure to high temperatures. The concrete cover around the steel bar is considered as a thick-walled cylinder whose inner surface is subjected to uniform pressure. The cylinder is further divided into a partially cracked interior portion and an uncracked outer portion under a pull-out loading. The tensile softening behavior of the cracked interior portion and the material property degradations of steel and concrete after exposure to high temperatures are considered. The proposed model has demonstrated its accuracy and reliability in predicting the residual bond strengths of steel bars by comparing the analytical predictions with pull-out tests results from the literature. A local bond-slip relationship is then established and used in a finite element analysis. The finite element results are then compared with measured load–displacement curves that were obtained from pull-out tests in the literature, providing a verification to the proposed bond-slip constitutive law.